Pedagogy for Teaching Linguistics: Forum Table - Aparicio, Marco; Aguilar, Jorge; Moreno, Tom; Guerrero, Orlando (CIEX JOURNAL, 2018)
The practice of second language teaching requires having the knowledge of several areas, among which the knowledge of the area of Linguistics is basic for the language teacher to be able to take the best decisions for the application of the language teaching methodology in the second language classroom. Despite this, it is usual to observe that: (1) Second language teachers seem not to have the necessary linguistic knowledge which can appropriately support their knowledge and use of the Second Language Teaching methodology; (2) the students enrolled in Second Language Teacher Development programs have difficulties for understanding the linguistic theories and concepts, as well as their application in the practice of second language teaching; (3) both students enrolled in Second Language Teacher Development programs and second language teachers have the idea that the knowledge of the area of linguistics is difficult and, so they tend to avoid getting in contact with the area of linguistics, and tend not to speak about this area with their colleagues. The purpose of this forum is to start a professional discussion about how the knowledge of the area of linguistics should be taught in Second Language Teacher Development programs. In this regard, the speakers will share information about pedagogic techniques and strategies for teaching linguistics that may have been reported in the literature, as well as they will share information about their own experience teaching linguistics to students professionalizing in the area of second language teaching.